Tongluo Yishen Decoction Ameliorates Renal Fibrosis via NLRP3-Mediated Pyroptosis In Vivo and In Vitro - Jia, Qi; Zhang, Xiaoyu; Hao, Gaimei; Zhao, Yun; Lowe, Scott; Han, Lin; Qin, Jianguo (Frontiers in Pharmacology, 2022)
Purpose: In this study, we investigated the mechanism of Tongluo Yishen (TLYS) decoction in more detail, from the perspective of pyroptosis in the unilateral ureteral ligation (UUO) model and the hypoxia-induced renal tubular epithelial (NRK-52E) cell. Method: The UUO model was used, and after 14 days of TLYS intervention, rats were tested for blood creatinine and urea nitrogen, HE staining was used to observe the pathological changes in the kidney, Masson staining was used to assess the degree of interstitial fibrosis, western blot was used to detect the changes of α-smooth muscle actin (α-SMA) protein expression level, immunohistochemistry and western blot detected the changes in protein expression levels of NOD-like receptor protein 3 inflammasome (NLRP3), gasdermin D (GSDMD), cysteinyl aspartate specific proteinase (caspase-1), interleukin 18 (IL-18) and interleukin 1β (I L-1β). A hypoxia model was created using NRK-52E cell, and after different concentrations of TLYS decoction intervention, the changes in the expression levels of pyroptosis were used with immunofluorescence and western blot methods. Results: TLYS improved renal function, delayed the advancement of renal interstitial fibrosis, and inhibited pyroptosis in UUO rats. Furthermore, we observed that TLYS can mitigate hypoxia-induced NRK-52E cell damage via the suppression of the NLRP3-mediated pyroptosis. Conclusion: TLYS decoction exert renoprotective effects by inhibiting NLRP3-mediated pyroptosis.